Blockchain discover the technology behind smart contracts, wallets, mining and cryptocurrency (including Bitcoin, Ethereum, Ripple, Digibyte and others) - White, Abraham K. ([Abraham K. White], 2018)
"Discover the technology that will change the futureu2026 In addition to blockchain technology, this book also explains the Internet of Things, smart contracts, the Ledger of Things, as well as the application of these technologies. After delving into the conceptual analysis of how these technologies work, this book provides guided, practical instruction on working with blockchain and cryptocurrencies, such as creating and executing a smart contract and opening an Ethereum wallet, with steps that are designed to help readers get started investing in cryptocurrencies. If you want to learn more about blockchain and whether it is worth investing in, then this book will definitely help you make an informed decision!" --